2023
DOI: 10.3390/polym15081949
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Performance of a Step-Lap Joint under Tensile Load: A Numerical Study

Abstract: In many technical domains, adhesively bonded joints have been employed extensively. These joints perform poorly against peel stresses despite having good shear characteristics. A step-lap joint (SLJ) is one of the techniques used to reduce the peel stresses at the edges of the overlap area to avoid damages. In these joints, the butted laminations of each layer are successively offset in succeeding layers in the same direction. Bonded joints are subjected to cyclic loadings in addition to static loads. It is di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Figure 7 presents the damage distribution, i.e., SDEG, on the adhesive layer when the maximum load is attained on the left punch. For all of them, the damage started from the right end of the adhesive layer and later from the left side, then from both sides, propagating towards to the center [20]. An interesting point here is that for StLJ-1step and StLJ-3step, the crack propagated more from the right side towards to the center of the adhesive layer when compared to the other two configurations.…”
Section: Effect Of Number Of Stepsmentioning
confidence: 80%
“…Figure 7 presents the damage distribution, i.e., SDEG, on the adhesive layer when the maximum load is attained on the left punch. For all of them, the damage started from the right end of the adhesive layer and later from the left side, then from both sides, propagating towards to the center [20]. An interesting point here is that for StLJ-1step and StLJ-3step, the crack propagated more from the right side towards to the center of the adhesive layer when compared to the other two configurations.…”
Section: Effect Of Number Of Stepsmentioning
confidence: 80%
“…Schieppati et al [24] studied the fatigue properties of NBR, and found that the higher the temperature, the faster the crack growth rate, while the crack growth rate changed slightly at 25 • C~40 • C. Liu Xiangnan et al [25] conducted uniaxial tensile fatigue tests on dumbbell-shaped natural rubber specimens, and found that the fatigue life was dispersive under the same conditions, so three probability distribution models, namely normal distribution, lognormal distribution and Weibull distribution were used to quantify the life distribution. Demiral et al [26] made a finite element simulation of a bonded joint and used the user-defined UMAT subroutine of ABAQUS/Standard to link the static damage and fatigue damage models of the bonded zone to express the response of the bonded layer. Fang Yunzhou et al [27] adopted the Arrhenius model, introduced the high temperature aging factor into the fatigue model with the engineering strain peak as the damage parameter, and accurately predicted the fatigue life of rubber bushing using finite element analysis.…”
Section: The Effect Of Temperature On Rubber Fatiguementioning
confidence: 99%
“…Here, ∆D max , the maximum damage increase, was selected to be 0.005, where such a smaller value resulted in more precise results [25]. Ultimately, the total damage was equal to the summation of static and fatigue damages, D total = D static + D i+∆N i .…”
Section: Numerical Modellingmentioning
confidence: 99%